1992
DOI: 10.1101/gad.6.10.1899
|View full text |Cite
|
Sign up to set email alerts
|

I kappa B interacts with the nuclear localization sequences of the subunits of NF-kappa B: a mechanism for cytoplasmic retention.

Abstract: NF-~B is an inducible transcription factor comprised of a 50-kD (pS0) and a 65-kD (p65) subunit. Induction of NF-KB activity, which is a critical event in many signal transduction pathways, involves release from a cytoplasmic inhibitory protein, IKB, followed by translocation of the active transcription factor complex into the nucleus. Earlier studies suggested that IKB targets the p65 subunit of NF-KB. However, we demonstrate by in vitro and in vivo methods that the recently cloned IKB/MAD-3 interacts with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
527
2
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 692 publications
(548 citation statements)
references
References 50 publications
13
527
2
6
Order By: Relevance
“…In some experimental systems p50/p50 homodimers activated transcription from promoters with speci®c kB sites (Collart et al, 1990;Fujita et al, 1992Fujita et al, , 1993Kretzschmar et al, 1992;Schouten et al, 1995;Ten et al, 1992). In other experimental systems these homodimers were unable to activate gene transcription (Beg et al, 1992;Franzoso et al, 1992;Kang et al, 1992;Plaksin et al, 1993;Schmitz and Baeuerle, 1991). It seems that p50/p50 displays high a nity binding for many distinct kB motifs but provides a strong transcriptional activation only when adopting a speci®c conformation induced by certain kB motifs but not others (Fujita et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some experimental systems p50/p50 homodimers activated transcription from promoters with speci®c kB sites (Collart et al, 1990;Fujita et al, 1992Fujita et al, , 1993Kretzschmar et al, 1992;Schouten et al, 1995;Ten et al, 1992). In other experimental systems these homodimers were unable to activate gene transcription (Beg et al, 1992;Franzoso et al, 1992;Kang et al, 1992;Plaksin et al, 1993;Schmitz and Baeuerle, 1991). It seems that p50/p50 displays high a nity binding for many distinct kB motifs but provides a strong transcriptional activation only when adopting a speci®c conformation induced by certain kB motifs but not others (Fujita et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ®nding that IkB-a de®cient mice exhibited severe dermatitis accompanied by strong epidermal hyperplasia and hyperkeratosis (Beg et al, 1995;Klement et al, 1996) strongly suggests that NF-kB promotes keratinocyte proliferation. Moreover, the skin phenotype in mice lacking both IkB-a and p50 subunit of NF-kB developed with dramatic delay in comparison with IkB-a 7/7 mice (Beg et al, 1995). This partial rescue of the phenotype by the lack of p50 indirectly indicates that p50 is speci®cally important for NF-kB-mediated regulation of keratinocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…All these proteins are characterized by the presence of repetitive sequences named`Ankyrin Repeats' because they are similar to the human protein ankyrin (Lux et al, 1990). The Ankyrin domain of the IkB proteins, with the exception of Bcl-3, covers the nuclear localization signal of NF-kB proteins and sequesters them in the cytoplasm (Haskill et al, 1991;Beg et al, 1992;Ganchi et al, 1992;Henkel et al, 1992;Lenardo and Siebenlist, 1994). A large number of signals can liberate NF-kB from its IkB inhibitor and thus allow NF-kB nuclear translocation and transactivation of target genes (Baldwin, 1996;Siebenlist, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that their actual entry is mediated by the importins/NPC complexes [72]. Unlike Stats and Smads, NFκB proteins have recognizable NLS [25,69,73,74]. Both importin α3 and α4 have been shown to mediate their nuclear translocation [72].…”
Section: −3 Nuclear Translocation Of Nfκbmentioning
confidence: 99%